Análise genotípica e filogenética com base nos genes do pilus tipo IV de Moraxella bovis e da citotoxina de M. bovis, Moraxella bovoculi e Moraxella ovis - Farias, Luana D'Avila (2015)
Historically, infectious bovine keratoconjunctivitis (IBK) was believed to be under the exclusive competence of Moraxella bovis. However, the roles of other species of Genus Moraxella are also being considered in the pathogenesis of IBK, such as Moraxella ovis and particularly Moraxella bovoculi. This thesis describes phylogenetic and genotypic analysis based on the genes encoding type IV pili Q- and I-type (TfpQ/I) of M. bovis and cytotoxin of M. bovis (MbxA), M. bovoculi (MbvA) and M. ovis (MovA). The distinction between M. bovis, M. bovoculi and M. ovis was previously performed by PCR (16S-23S intergenic region) according to the protocol established in the literature. Then, there is described a molecular analysis based on the 3' region of genes tfpQ/I (including α1-C N-terminal subdomain and C-terminal domain) of 16 field strains and five vaccine strains of M. bovis from South America. All 47 sequences of tfp Q- and I-type genes analyzed resulted in 31 alleles designated 1 to 31. The phylogenetic reconstruction resulted in a distinction of 31 alleles in eleven groups (designated A through J and Epp). The analysis of the deduced amino acid sequence (aa) of the C-terminal region showed similarity levels between 67 and 100% within the groups, while the analysis of the D region (C-terminal subunit) resulted in levels of similarity between 60 and 100%. In addition, a phylogenetic analysis based on the 3' region of the cytotoxin gene was performed to investigate the genetic relationship among M. bovis (n = 17), M. bovoculi (n = 11) and M. ovis (n = 7) strains and reference strains. Phylogenetic reconstruction allowed the differentiation among species, and the older M. bovoculi strains remained in branch closer to M. bovis strains. The amino acid similarity level among the MbxA sequences stood at an average of 99.9%, while among the MbvA and MovA sequences the similarity was respectively 98.8% and 99.3%. The similarity between MbvA and MovA was 96.6%, while MbxA for MbvA and MovA was 77.6%. Thus, it is possible to conclude that the tfp gene may be inferred suitable for differentiate among M. bovis strains, while the cytotoxin-encoding gene is suitable for phylogenetic classification of M. bovis, M. bovoculi and M. ovis strains and perhaps for understanding the evolutionary relationships among three species.